L’envol du panda ? Aviation civile chinoise et innovation - Jean-Paul MARÉCHAL, (MONDE CHINOIS NOUVELLE ASIE, 2020)
The purpose of this article is to analyze the Chinese strategy for technological catch-up in the field of civil aviation. We will do this in five steps. We will begin with a look back at the first decades of Chinese aeronautical history. Then we will analyze the industrial policy which, from the 1990s, led to the constitution of the two national champions, AVIC and COMAC. Thirdly, we will decipher the flagship program that is the C919. In a fourth, we will study the place of Chinese production in the world market. Finally, we will take stock of the reality of Chinese technological “looting” in the field of aircraft construction .